Methodology for Analyzing the Capability of Microorganism to Deal with Polystyrene Waste Through Biodegradation - Balqis Ramadhillah; Filson Maratur Sidjabat (Fakultas Teknik, 2022)
The challenge to solve plastic pollution in Indonesia has always been a concern for environmentalist, Moreover, the polystyrene plastic resin which has been proved as the major contributor for marine debris in Indonesia coastline. Using findings from prior studies, this paper attempts to discuss biodegradation by microorganisms in dealing with polystyrene waste. The analytical methodologies for measuring the capability of microorganisms in degrading polystyrene is examined. The most frequent and common analytical methodology used are the FTIR spectroscopy, SEM, GPC, and TGA. These analytical methodologies along with other complementary methods have proved that specific bacteria, fungi, and worms are capable of degrading polystyrene waste. This perhaps may be one of the less toxic, environmentally friendly solutions for plastic pollution in Indonesia.